NILAI PERUSAHAAN: CURRENT RATIO, DEBT TO ASSET RATIO DAN RETURN ON EQUITY MELALUI FINANCIAL DISTRESS - Deden Edwar Yokeu Bernardin; Cie Tia Nugina Rahmawati (LPPM Universitas Adhirajasa Reswara Sanjaya, 2023)
The Covid-19 pandemic has had a negative impact on the corporate sector in Indonesia, which could trigger financial difficulties and keep companies away from the attention of investors. This study aims to examine the effect of the Current Ratio, Debt To Asset ratio and Return On Equity on firm value and their impact on Financial Distress at PT Salingka Global Indonesia. The research method used is descriptive verification method with a quantitative approach. The results show that partially the Current Ratio, Debt To Asset ratio, and Return On Equity have a significant effect on Financial Distress but the firm value has no significant effect. Simultaneously the Current Ratio, Debt To Asset ratio and Return On Equity have a significant effect on Financial Distress, but have no effect on firm value